Design Thinking Research Building Innovators - Plattner, Hasso; Meinel, Christoph; Leifer, Larry; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
Design thinking as a user-centric innovation method has become more and more widespread during the past years. An increasing number of people and institutions have experienced its innovative power. While at the same time the demand has grown for a deep, evidence-based understanding of the way design thinking functions. This challenge is addressed by the Design Thinking Research Program between Stanford University, Palo Alto, USA, and Hasso Plattner Institute, Potsdam, Germany. Summarizing the outcomes of the 5th program year, this book imparts the scientific findings gained by the researchers through their investigations, experiments, and studies. The method of design thinking works when applied with diligence and insight. With this book and the underlying research projects, we aim to understand the innovation process of design thinking and the people behind it. The contributions ultimately center on the issue of building innovators. The focus of the investigation is on what people are doing and thinking when engaged in creative design innovation and how their innovation work can be supported. Therefore, within three topic areas, various frameworks, methodologies, mindsets, systems and tools are explored and further developed. The book begins with an assessment of crucial factors for innovators such as empathy and creativity, the second part addresses the improvement of team collaboration and finally we turn to specific tools and approaches which ensure information transfer during the design process. All in all, the contributions shed light and show deeper insights how to support the work of design teams in order to systematically and successfully develop innovations and design progressive solutions for tomorrow.
Introduction -- Assessing Influential Factors in Design Thinking -- Empowering Team Collaboration -- Support in Information Transfer.
Keywords: Economics; Software engineering; Information Systems; Management information systems; Economics/Management Science; Business Information Systems; Innovation/Technology Management; Software Engineering; Management of Computing and Information Systems